Genome editing for healthy crops: traits, tools and impacts - Yıldırım, Kubilay; Miladinović, Dragana; Sweet, Jeremy; Akin, Meleksen; Galović, Vladislava; Kavas, Musa; Zlatković, Milica; de Andrade, Eugenia (Frontiers in Plant Science, 2023)
Crop cultivars in commercial use have often been selected because they show high levels of resistance to pathogens. However, widespread cultivation of these crops for many years in the environments favorable to a pathogen requires durable forms of resistance to maintain “healthy crops”. Breeding of new varieties tolerant/resistant to biotic stresses by incorporating genetic components related to durable resistance, developing new breeding methods and new active molecules, and improving the Integrated Pest Management strategies have been of great value, but their effectiveness is being challenged by the newly emerging diseases and the rapid change of pathogens due to climatic changes. Genome editing has provided new tools and methods to characterize defense-related genes in crops and improve crop resilience to disease pathogens providing improved food security and future sustainable agricultural systems. In this review, we discuss the principal traits, tools and impacts of utilizing genome editing techniques for achieving of durable resilience and a “healthy plants” concept.